Study on Intercropping Carrot with Groundnut Under Different Row Arrangements - Mondal, MRI; Begum, F; Alam, MM (Bangladesh Journal of Agricultural Research, 2012)
Burirhat, Rangpur during two consecutive seasons of 2004-05 and 2005-06, respectively, to find out suitable row arrangement of carrot with groundnut for higher yield and economic return. There were six treatments, such as sole groundnut, sole carrot, one row of carrot in between two normal rows of groundnut, two rows of carrot in between two normal rows of groundnut, two rows of groundnut alternated with two rows of carrot and three rows of groundnut alternated with three rows of carrot. Results showed that monoculture produced the highest yields of individual crops but in intercropping system the highest groundnut equivalent yield (10.63 t/h and 11.10 t/ha) was obtained from two rows of carrot in between two rows of groundnut. The maximum land equivalent ratio (1.67 and 1.74), the highest gross return (Tk.212600/ha and Tk. 248400/ha) and net return (Tk.184881/ha and Tk.211680) were also obtained from the intercropping treatment with two rows carrot in between two normal rows of groundnut. But due to higher cost in this treatment, maximum benefit cost ratio (7.09 and 7.01) was obtained from the intercropping treatment with one row carrot in between two normal rows of groundnut in both the years. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11223 Bangladesh J. Agril. Res. 37(2): 215-223, June 2012